Ebola Virus Shed Glycoprotein Triggers Differentiation, Infection, and Death of Monocytes Through Toll-Like Receptor 4 Activation. (31st July 2018) - Iampietro, Mathieu; Santos, Rodrigo I; Lubaki, Ndongala Michel; Bukreyev, Alexander
Abstract : The study demonstrates that treatment of monocytic cells with Ebola virus shed glycoprotein promotes their differentiation resulting in increased infection and cell death. The effects were inhibited by blocking Toll-like receptor 4 pathway. Abstract: A better understanding of the mechanisms used by Ebola virus to disable the host immune system and spread the infection are of great importance for development of new therapeutic strategies. We demonstrate that treatment of monocytic cells with Ebola virus shed glycoprotein (GP) promotes their differentiation resulting in increased infection and cell death. The effects were inhibited by blocking Toll-like receptor 4 pathway. In addition, high levels of shed GP were detected in supernatants of cells treated with Ebola vaccines. This study highlights the role of shed GP in Ebola pathogenesis and also in adverse effects associated with Ebola vaccines.